2009
DOI: 10.1016/j.pain.2009.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin-evoked iCGRP release from human dental pulp: A model system for the study of peripheral neuropeptide secretion in normal healthy tissue

Abstract: The mechanisms underlying trigeminal pain conditions are incompletely understood. In vitro animal studies have elucidated various targets for pharmacological intervention; however, a lack of clinical models that allow evaluation of viable innervated human tissue has impeded successful translation of many preclinical findings into clinical therapeutics. Therefore, we developed and characterized an in vitro method that evaluates the responsiveness of isolated human nociceptors by measuring basal and stimulated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 76 publications
3
45
0
Order By: Relevance
“…In agreement with a previous study we found no significant effect for any of these individual factors (21). This finding is important because it suggests that excluding subjects meeting these specific criteria would be unlikely to reduce the observed variability in the primary outcome, i.e.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with a previous study we found no significant effect for any of these individual factors (21). This finding is important because it suggests that excluding subjects meeting these specific criteria would be unlikely to reduce the observed variability in the primary outcome, i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies using human dental pulp from extracted teeth have completely dissociated the dental pulp from the surrounding hard tissues (21,22). In this study, the use of ex vivo tooth slices maintains the gross anatomical relationships present in the pulpo-dentin complex, specifically the orientation of the nerve endings to dentinal tubules and odontoblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nociceptors innervating the human dental pulp express TRPV1. These neurons also contain CGRP [48]. Furthermore, 5-HT receptor protein is present in human pulp as reported by western blot [49].…”
Section: Does Serotonin Modulate Trpv1 Channels?mentioning
confidence: 98%
“…For example, using a recently-developed in vitro superfusion method to measure proinflammatory peptide release from human dental pulp from extracted teeth [30], Loyd et al [67] reported sex differences in inflammation-induced proinflammatory peptide release that was dependent on stage of menstrual cycle. Specifically, inflammatory mediator-evoked proinflammatory peptide release was highest in amenstrual females and females in the last week of menses [67].…”
Section: Spinal Antinociception Is Sexually Dimorphic and Dependent Omentioning
confidence: 99%